Vitamin D Levels and Insulin Resistance among Nigerian Men with Type-2 Diabetes mellitus - Abbiyesuku FM; Olawale OO; Agbakwuru AN; Olooto WE (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2016)
Background: A number of studies have shown a high prevalence of insufficient vitamin D levels in humans in the North American, European and Asian regions. Various research works have also shown that low serum vitamin D levels play a major role in the pathogenesis of chronic, non-infective illnesses such as diabetes mellitus and cancer. Objective: This study was aimed at assessing the serum vitamin D status in relation to glucose homeostasis among men with Type-2 Diabetes mellitus and normal controls. Methods: This comparative cross-sectional study included 80 men with confirmed diagnosis of Type-2 diabetes mellitus and 49 normal adult male controls. Serum 25-hydroxy vitamin D, fasting serum C-peptide and fasting plasma glucose levels were measured in both study groups. Results: There was a significant difference between the mean serum 25-OH vitamin D levels among the cases (36.55ng/mL) and the controls (42.96ng/mL) (p = 0.001). All the four 25-OH vitamin D-deficient subjects had diabetes. In the diabetes group, 43.8% had a normal insulin resistance compared to 61.8% of the control group (p = 0.054). In the diabetes group, 73.8% had sufficient vitamin D, 21.2% had insufficient vitamin D and 5% had vitamin D deficiency. In the control group, there was a significant negative correlation between serum 25-OH vitamin D and BMI and fasting plasma glucose. The mean HOMA2IR value for the diabetes group (3.09) was higher than the value for the controls (2.40). Conclusion: The mean serum 25-OH vitamin D level in the diabetes group was lower than that of the control group hence, hypovitaminosis D may be a contributor to the onset of diabetes mellitus among Nigerian men.